GANGGUAN PENDENGARAN AKIBAT BISING - Lintong, Fransiska (Jurnal Biomedik : JBM, 2009)
Abstract: Noise induced hearing loss is often found among industrial workers all over the world, especially in developing countries, such as Indonesia. The permitted maximum limit of noise for a human being is 80 dB. Noise with a high intensity that occurs for a long time can cause some changes in metabolic processes and the blood supply in the organ of Corti. The impacts of these changes are damage and degeneration of hair cells, and in the long run, the total destruction of this organ and permanent hearing loss. Effects of noise to this sense organ are in the forms of acoustic trauma, noise-induced temporary threshold shift, and noise-induced permanent threshold shift. Noise induced hearing loss is a senso-neural deafness, and is generally bilateral. Key words: noise, organ of Corti, permanent loss, senso-neural deafness Abstrak: Gangguan pendengaran akibat bising sering dijumpai pada pekerja industri di seluruh dunia, terlebih lagi di negara berkembang seperti Indonesia. Ambang batas maksimum aman dari bising bagi manusia adalah 80 dB. Bising dengan intensitas tinggi yang berlang-sung dalam waktu lama akan menyebabkan perubahan metabolisme dan vaskuler. Sebagai akibat terjadi robekan sel-sel rambut organ Corti dan kerusakan degeneratif sel-sel tersebut, yang kemudian berlanjut dengan destruksi total dari organ tersebut dan kehilangan pen-dengaran yang permanen. Efek bising terhadap pendengaran dapat berupa trauma akustik, perubahan ambang pendengaran akibat bising yang berlangsung sementara, dan perubahan ambang pendengaran akibat bising yang berlangsung permanen. Gangguan pendengaran yang terjadi akibat bising adalah berupa tuli senso-neural yang biasanya bilateral. Katakunci: Kebisingan, organ corti, permanen, tuli senso-neural